Supplemental 25-Hydroxycholecalciferol Is More Effective than Cholecalciferol in Raising Serum 25-Hydroxyvitamin D Concentrations in Older Adults. Issue 1 (13th September 2019) - Graeff-Armas, Laura A; Bendik, Igor; Kunz, Iris; Schoop, Rotraut; Hull, Sarah; Beck, Mareike
ABSTRACT: Background: There are few studies directly comparing the pharmacokinetics of 25-hydroxycholecalciferol [25(OH)D3] to cholecalciferol (D3). Objectives: The primary objectives were to compare the effectiveness of D3 and 25(OH)D3 in raising 25-hydroxyvitamin D [25(OH)D] serum concentrations and achieving steady state. Methods: This was a randomized, double-blind, active comparator trial of 91 participants (53 females, 38 males), aged 63.3 ± 7.9 y. 25(OH)D3 (10, 15, and 20 µg) and D3 (20 µg) were dosed daily for 6 mo followed by 6 mo of washout. Frequent measurements of serum 25(OH)D were performed. Pharmacokinetic parameters were fitted for each individual and the treatment average was modeled with linear regression using the individual baseline level, sex, and gender as covariates. Results: Mean baseline 25(OH)D was similar in all groups (47.1–49.5 nmol/L). Increases in 25(OH)D to steady state were higher in the 25(OH)D3 groups than in the D3 group [least squares (LS) means (95% CI): 50.1 (43.3–58.0), 72.5 (64.3–81.7), 97.4 (86.6–109.6) nmol/L in 10, 15, and 20 µg/d and 38.7 (33.1–45.2) nmol/L in the D3 group; P = 0.0173, P < 0.0001, P < 0.0001]. The rate to reach steady state was similar in all groups, but the time to reach 25(OH)D concentrations of 75 nmol/L was faster in the higher-dosed 25(OH)D3 groups than in the D3 group (7 and 10 d compared with 40 d, P < 0.0001 and P < 0.0001 for 15 and 20 µg/d). The rate of elimination was 59–109% higher in the 25(OH)D3 groups than in the D3 group. The area under the curve (AUC)/µg dose demonstrated that 25(OH)D3 was 3 times as effective as D3 at raising 25(OH)D concentrations. Conclusions: 25(OH)D3 is ∼3 times as effective as D3 at raising 25(OH)D concentrations. Once supplementation is discontinued, the elimination rate of 25(OH)D3 is faster than D3. This trial was registered at clinicaltrials.gov as NCT02333682.